Análisis del problema de la legitimidad en la concepción política de John Rawls - Guevara Arroyo, Alejandro (2014)
The paper proposes an analytical reconstruction of the legitimacy criterion as a test for the principles of justice for social institutions and elaborates on Rawls’ probable response. In addition, the paper critically examines (i) the truth regarding some empirical premises in Rawls’s political theory and (ii) the inferential validity of some of the main responses to the legitimacy problem.